PARQUES TECNOLÓGICOS REGIONALES EN EL PERÚ * - Espinoza Herrera, Nemesio (2007)
The study raises like objective the one to observe and to analyze the conditions that are necessary for the constitution of technological parks in the regions of Peru within the frame of national decentralization and to raise some considerations that allow to promote the real entailment between State-company-university on the base of science, technology and innovation. Method: for aims of the present study it has been visited the different regions from the country to observe the situation of the interrelation between the State, the companies and the universities in the process of regional the economic and social development. Results: It does not exist in Peru any experience related to the technological parks nor to constitute them, done initiatives that the situation of scientific and technological delay of the country corroborates. Conclusion: In the context of the society of the own knowledge of Century XXI and the third millenium the imperative necessity is manifest to promote the constitution of technological parks in the regions of Peru in order to promote the development maintained and sustainable of the country on science base, technology and innovation.